Visigoths and Romans after 410 - Székely, Melinda (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In 410, the Roman Empire was shaken to its core after Rome was sacked by the Visigoths. The Barbarian attacks and the emergence of the usurpers created a severe crisis in the Western Roman Empire. The study of contemporary authors reveals that the crisis engendered a change in attitudes. For the Empire to be reconstructed, the traditional Roman, anti-barbarian attitude had to be changed, and living together and cooperating with the Goths was now a must. The change in attitude can be detected in Orosius’ work, a formerly anti-barbarian author who places Athaulf’s speech at Narbonne in the centre. The marriage of the Visigoth king with Galla Placidia (414), the Romanization of the Goths, their imperial service, and their new relationship with Romans as described in the speech is all a solid basis for a reestablishment of Goth-Roman relations and the creation of a new federal agreement, which actually took place in 418.